Clinical and health status outcomes among patients treated with single as compared to multivessel angioplasty during chronic total occlusion percutaneous coronary interventions: a report from the OPEN CTO registry. Issue 2 (23rd December 2020) - Riley, Robert F.; Sapontis, James; Karmpaliotis, Dimiti; Nicholson, William J.; Moses, Jeffrey W.; Gosch, Kensey; Lombardi, William L.; Salisbury, Adam C.; McCabe, James M.; Grantham, J. Aaron
Abstract : Background: Patients with coronary chronic total occlusions (CTO) often have multivessel coronary artery disease. We utilized the OPEN CTO study to evaluate patients who underwent single-vessel versus multivessel percutaneous coronary intervention (PCI) during CTO PCI. Methods: Patients were considered to have undergone single-vessel CTO PCI if they underwent target-vessel only CTO PCI. Patients who underwent multivessel PCI during their index CTO PCI procedure were considered to have undergone multivessel PCI. The additional lesions treated in the multivessel group could be either a separate CTO lesion in a separate epicardial vessel or PCI attempt of any non-CTO stenosis during the same index procedure. Multivariate regression models were used to evaluate predictors of technical success, in-hospital major adverse cardiac and cerebrovascular events (MACCE), and health status measures. Results: Eighty hundred twenty-one patients underwent single-vessel CTO PCI and 179 (17.9%) underwent multivessel PCI during their CTO PCI procedure. Baseline comorbidities, index CTO lesion complexity, and successful crossing strategies used were similar between the two groups. Total procedural time (142.6 versus 115.9 minutes, P < 0.01) and contrast administered (293.8 versus 255.0 ml, P < 0.01) were increased in the multivessel CTO PCI group. Single-vessel versus multivessel PCI during these cases did not affect the likelihood of achieving technical success [odds ratio (OR) 1.05, 95% confidence interval (CI) 0.63–1.75] nor the risk for MACCE (OR 1.23, 95% CI 0.72–2.11). Quality of life (QOL) metrics were similar between the two groups at baseline and 30-day follow-up. Conclusion: There were no significant differences in technical success, in-hospital MACCE rates, or QOL metrics at 30-day follow-up for patients who underwent single-vessel versus multivessel PCI during CTO PCI.